2016
DOI: 10.12957/reuerj.2016.11050
|View full text |Cite
|
Sign up to set email alerts
|

Características da violência exercida por adolescentes escolares [Characteristics of violence by school teenagers] [Características de la violencia por parte de estudiantes adolescentes]

Abstract: RESUMO Objetivo: descrever as características da violência exercida por adolescentes escolares da capital de Mato Grosso, Brasil. Método: estudo transversal, realizado em 2012, com uma amostra de 2.786 adolescentes escolares. Os dados foram coletados por meio de questionário fechado e autoaplicável, processados pelo Epi-Info, e para as análises bivariadas foi considerado o valor de p<0,05. O projeto foi aprovado por Comitê de Ética em pesquisa número CAAE 01986012.9.0000.5541. Resultados: 334 adolescentes exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…These include violence in the home environment, exploitation of minors, and exposure to alcohol, drugs, trafficking, theft, and other harmful influences. 12 The data from this research highlight the problematic nature of adolescents as perpetrators of violence, with over half of the participants reporting they had engaged in violence at least once. A study 13 of 2,786 adolescents from 17 public schools in Mato Grosso, Brazil, found that 1,236 participants (44.36%) reported having been exposed to violence in the roles of victim, perpetrator, and both simultaneously.…”
Section: Discussionmentioning
confidence: 86%

Profile of violence perpetrated by adolescents

Ronildo da Costa,
Mccarthy de Oliveira Silva,
Cruz Neto
et al. 2024
Pensar Enf
“…These include violence in the home environment, exploitation of minors, and exposure to alcohol, drugs, trafficking, theft, and other harmful influences. 12 The data from this research highlight the problematic nature of adolescents as perpetrators of violence, with over half of the participants reporting they had engaged in violence at least once. A study 13 of 2,786 adolescents from 17 public schools in Mato Grosso, Brazil, found that 1,236 participants (44.36%) reported having been exposed to violence in the roles of victim, perpetrator, and both simultaneously.…”
Section: Discussionmentioning
confidence: 86%

Profile of violence perpetrated by adolescents

Ronildo da Costa,
Mccarthy de Oliveira Silva,
Cruz Neto
et al. 2024
Pensar Enf
“…Tal fato pode ser justificado pelo movimento crescente de luta e desmistificação que há em relação a mulheres serem consideradas o "sexo frágil". Nesse sentido, faz-se necessário promover ações de prevenção da violência entre adolescentes, com sua sensibilização para resolução de conflitos com base na tolerância e no diálogo em detrimento da utilização de atos violentos (Godoy et al, 2016).…”
Section: Abuso Físico Parental Entre Os Pais E Entre Os Paresunclassified